2023
DOI: 10.3389/fpsyg.2023.1115108
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and bilingual children’s home language environment: Digital media, socioeconomic status, and language status

Abstract: Input is considered crucial in bilingual children’s language development. This is especially true for bilingual children’s mother tongue language learning given its common reduction in input opportunities due to the dominance of one language within society, as seen in countries and regions from Wales to Singapore. Previous studies tend to focus on the quantity and quality of conventional active communication and resources (e.g., speaking and reading with parents) on bilingual children’s language development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Socioeconomic status seems to be a key factor in this respect since some of the families with a low income or who are unemployed were not able to offer the same educational opportunities for their children in comparison with some other well-off families. This finding is in line with findings of Sun et al (2023), who also reported differences between families with high and low socioeconomic statuses. However, in the Swedish data, the socioeconomic differences seemed to be less pronounced (however, it needs to be investigated with statistical data).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Socioeconomic status seems to be a key factor in this respect since some of the families with a low income or who are unemployed were not able to offer the same educational opportunities for their children in comparison with some other well-off families. This finding is in line with findings of Sun et al (2023), who also reported differences between families with high and low socioeconomic statuses. However, in the Swedish data, the socioeconomic differences seemed to be less pronounced (however, it needs to be investigated with statistical data).…”
Section: Discussionsupporting
confidence: 92%
“…The increased use of Mandarin between the child and his/her parents in the COVID sample was noted as compared to that of the pre-COVID sample. In contrast, a study by Sun et al (2023) investigating the effects of COVID on language development in English-Mandarin bilingual children in Singapore showed no change in language input among nuclear members; however, the amount and frequency of conventional and digital media materials and activities increased during the pandemic, which is suggested to positively influence language proficiency in English, while weakening abilities in Mandarin in the post-COVID period.…”
Section: Family Language Policymentioning
confidence: 80%
See 1 more Smart Citation